2019
DOI: 10.1038/s41598-019-38568-w
|View full text |Cite
|
Sign up to set email alerts
|

Brg1 promotes liver regeneration after partial hepatectomy via regulation of cell cycle

Abstract: Brahma-related gene 1 (Brg1), a catalytic subunit of the SWItch/Sucrose Non-Fermentable (SWI/SNF) complex, is known to be involved in proliferative cell processes. Liver regeneration is initiated spontaneously after injury and leads to a strong proliferative response. In this study, a hepatocyte-specific Brg1 gene knockout mouse model was used to analyse the role of Brg1 in liver regeneration by performing a 70% partial hepatectomy (PH). After PH, Brg1 was significantly upregulated in wildtype mice. Mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…3c). Consistent with a previous report 21 , we found that loss of Brg1 did not affect liver homeostasis: indeed, liver/body weight ratio ( Fig. 3d), liver histology as well as hepatocyte proliferation (Fig.…”
Section: Loss Of Brg1 Does Not Affect Liver Homeostasissupporting
confidence: 93%
“…3c). Consistent with a previous report 21 , we found that loss of Brg1 did not affect liver homeostasis: indeed, liver/body weight ratio ( Fig. 3d), liver histology as well as hepatocyte proliferation (Fig.…”
Section: Loss Of Brg1 Does Not Affect Liver Homeostasissupporting
confidence: 93%
“…A follow-up study by Weng and colleagues have found that the long non-coding RNA LncFZD6 recruits BRG1 to the Frizzled6 promoter and the Wnt5a promoter to activate transcription, thereby driving liver cancer cell self-renewal ( Chen et al, 2018 ). More recently, Li N. et al (2019) and Wang et al (2019) have independently reported that BRG1 deficiency cripples liver regenerative response in mice accompanying down-regulation of β-catenin target genes related to cell proliferation. In light of our new data as summarized here, it is tempting to propose that BRG1 may be an integral part of the Wnt/β-catenin pathway functioning at several different levels (upstream and downstream of β-catenin) to amplify the signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that liver-specific deletion of β-catenin appears to render the mice more susceptible to the development of steatosis ( Behari et al, 2010 ) and HCC ( Wang et al, 2011 ), suggesting that any benefit of targeting β-catenin in the intervention of FH has to be weighed against its potential risks. We and others have previously shown that β-catenin relies on BRG1 to regulate the transcription of pro-proliferative genes in hepatocytes and to promote liver regeneration ( Li et al, 2019a ; Wang et al, 2019 ). Of note, multiple independent studies have implicated nephronectin in the regulation of cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%